CHARACTER EDUCATION FOR CONTEMPORARY URBAN MUSLIM STUDENTS: A COMPARATIVE STUDY AT UII AND UMY STUDENT ISLAMIC BOARDING SCHOOLS - Yusuf, Syaifulloh; Marhumah, Marhumah; Muslim, Aziz; Zainuddin, Nurkhamimi (AKADEMIKA: Jurnal Pemikiran Islam, 2025)
This study explores the implementation of character education in two urban-based student Islamic boarding schools affiliated with Islamic universities in Yogyakarta: The Islamic University of Indonesia (UII) and Ma’had Aly bin Abi Talib at Muhammadiyah University of Yogyakarta (UMY). While character education is a key feature in both classical and modern pesantren, this research investigates how these two institutions adapt their strategies to address the moral and social challenges faced by contemporary urban Muslim students in higher education contexts. Using a qualitative field approach, data were collected through interviews with caregivers, lecturers, and students, as well as observations and institutional document analysis during the 2022–2023 academic year. The findings reveal that UII emphasizes structured mentoring, leadership development, and integrative academic-religious programs, while UMY focuses on project-based learning through da’wah and tahfidz activities to shape students’ religious, social, and leadership character. Unlike pesantren in rural or traditional contexts, these urban-based institutions integrate academic demands, digital technology, and modern social dynamics into their character education framework. This study contributes to a contextual understanding of character development for contemporary urban Muslim students in Islamic higher education institutions.